2020
DOI: 10.1097/rnj.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Led Computerized Cognitive Training for Mild Cognitive Impairment: A Preliminary Study

Abstract: Purpose: This preliminary study aimed to compare the outcomes of an occupational therapist-led and a nurse-led computerized cognitive training (CCT) for mild cognitive impairment (MCI) in older adults. Design: A single-blind randomized controlled trial was performed. Methods: Participants 65 years of age and older with MCI were randomly assigned to a group led by an occupational therapist or by a nurse. Both groups received CCT for 4 weeks. Findings: Six participants in the occupational therapist-led group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In papers in which four or more items were found to be ‘high risk’, through author agreement, we decided to exclude them as papers for systematic review and data ex-traction. Accordingly, a total of 11 papers [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] were included except Styliadis (2015) for systematic review and data extraction ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In papers in which four or more items were found to be ‘high risk’, through author agreement, we decided to exclude them as papers for systematic review and data ex-traction. Accordingly, a total of 11 papers [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] were included except Styliadis (2015) for systematic review and data extraction ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the cases of MMSE and MoCA, similar categories such as orientation, memory registration, memory recall, and attention were measured. Papers excluded from the analysis were ‘difficult to clearly extract data between the experimental group and the control group’ [ 36 ], ‘papers where both the control group and the intervention group used ICT’ [ 38 , 43 ], or ‘the content of the intervention in the two groups was the same, but only the intervention provider was different’ [ 42 ]. Accordingly, after excluding these four studies, seven studies were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Following the assessment, 24 articles were excluded because the population/problem was not persons with dementia (n = 4), the intervention was not nurse-led (n = 7), and the study was not in the form of a trial (n = 13). Eleven publications were included in the final analysis, including three studies discovered from previous systematic reviews and the gray literature (Bailey et al, 2017;Callahan et al, 2006;Chien & Chan, 2009;Hsieh et al, 2010;Jha et al, 2013;Lai et al, 2004;Moon & Park, 2020;Oh et al, 2021;Pan & Chen, 2019;Samus et al, 2014;Thyrian et al, 2017). Appendix C in SDC provides an overview of the selection procedure.…”
Section: Study Selectionmentioning
confidence: 99%
“…Summary characteristics of included studies are found in Tables 1 and 2. The reviewed research was carried out in the United States (Bailey et al, 2017;Callahan et al, 2006;Samus et al, 2014), China (Chien & Chan, 2009;Lai et al, 2004;Pan & Chen, 2019), Taiwan (Hsieh et al, 2010), South Korea (Moon & Park, 2020;Oh et al, 2021), the United Kingdom (Jha et al, 2013), and Germany (Thyrian et al, 2017). A total of 1,372 patients with dementia in nursing homes, community centers, dementia resource centers, day care centers, or hospitals, or living at home, including those with Alzheimer's disease and moderate cognitive impairment, were represented in the eight trials, with the mean age ranging from 77.40 (5.90) to 86.20 (6.30) years in the intervention group and 77.25 (10.49) to 86.80 (7.30) years in the control group.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation